2015
DOI: 10.1016/j.rpor.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety of adjuvant intensity-modulated postoperative radiation therapy in endometrial cancer: Clinical data and dosimetric parameters according to the International Commission on Radiation Units (ICRU) 83 report

Abstract: IMRT Endometrial cancerBackground: IMRT in gynecological malignancies provides excellent dosimetric data, lower

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…7,8 Studies have suggested significantly lower rates of acute and late toxicity using postoperative pelvic IMRT. [9][10][11][12] IMRT compared to 3D planning is currently being studied in an ongoing clinical trial (RTOG 1203).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Studies have suggested significantly lower rates of acute and late toxicity using postoperative pelvic IMRT. [9][10][11][12] IMRT compared to 3D planning is currently being studied in an ongoing clinical trial (RTOG 1203).…”
Section: Introductionmentioning
confidence: 99%
“…The calculated and reconstructed doses were compared by determining the differences in DVH metrics. Recommendations of the International Commission on Radiation Units and Measurements (ICRU) report 83 were used to extract evaluation parameters for PTVs (D 98 , D 2 , D 50 , and D mean ) and maximum/mean doses (D max /D mean ) for OARs, in which D 2 is recommended to represent the approximate maximum dose for tandem OARs 27 . D 98 , D 2 , and D 50 are the doses covering 98%, 2%, and 50% of the PTVs/OARs volume 28,29 , respectively.…”
Section: Compass Reconstructionmentioning
confidence: 99%